Pibid Inglês Em Ação: Uma Experiência De Gamificação Em Uma Escola Pública (PERcursos Linguísticos, 2021)
Gamification, the application of game mechanisms on daily tasks, is defined by its proposal of transforming the everyday experience into a game, with the purpose of motivating positive reactions towards tasks, relating physical or digital rewards to their completion, bringing the possibility of arousing participants’ engagement (VIANNA et al, 2013). As part of the process of data collection for the development of the Programa Institucional de Bolsa de Iniciação à Docência (Pibid) – English subproject, 102 questionnaires were applied to students from the Colégio Estadual Jackson de Figueiredo, the school where we worked as grantees both as pre-service teachers and as area coordinator. The data collected through the questionnaires showed evidence that it would be interesting to implement gamification practices in the English classes at this school. It was then decided that the experience would be carried out through a competition called gincana, since it was adequate to the concepts of gamification and also allowed for the work on the contents previously planned by the teacher of that school. This text is a practical and reflexive report about the teaching of English that took place as part of Pibid, focusing on gamification, which showed to be an interesting practice, capable of transforming the relationship between the students and the teaching of English in that context.